Diabetes distress, emotional regulation, HbA1c in people with diabetes and A controlled pilot study of an emotion-focused behavioral therapy intervention in adults with type 2 diabetes. Issue 3 (June 2022) - Coccaro, Emil F.; Drossos, Tina; Kline, David; Lazarus, Sophie; Joseph, Joshua J.; de Groot, Mary
Abstract: Aim: One potential barrier for people with diabetes to reach glycemic goals is diabetes distress. Accumulating evidence suggests diabetes distress may be linked to individuals' emotion regulation capacities. Thus, we conducted two studies to elucidate a model for how emotion regulation impacts diabetes distress and A1c levels and determine preliminary effect size estimates for an intervention targeting poor emotion regulation on glycemic control. Methods: Study I used structural equation modeling to assess the cross-sectional relationships between these variables in a sample of 216 individuals with Type 1 and Type 2 diabetes. Study II built on findings from Study I that highlighted the role of emotion regulation capacities in diabetes distress and A1c by conducting a pilot study of an emotion-focused behavioral intervention compared to treatment as usual in a sample of individuals with Type 2 diabetes. Results: Study I examined two potential explanatory models with one of the models (Model II) showing a more comprehensive view of the data revealing a total effect of poor emotional regulation of 42% of all effects on A1c levels. Study II tested an emotion-focused behavioral intervention in patients with Type 2 diabetes compared to treatment as usual and found medium sized reductions in A1c levels and smaller reductions in diabetes distress that correlated with changes in emotion regulation. Conclusions: These studies suggest that, in people with diabetes, elevated A1c levels and diabetes distress are linked with poor emotion regulation. While the effect sizes from Study 2 are preliminary, an emotion-focused behavioral intervention may reduce both A1c and diabetes distress levels, through improvements in emotion regulation. Overall, these data suggest that targeting difficulties in emotion regulation may hold promise for maximizing improvement in diabetes distress and A1c in individuals with diabetes. Highlights: Diabetes-related distress (DD) is directly related to one's reduced ability to regulate negative emotional regulation (ER). Both DD and ER of negative emotion are related influence A1c levels to a greater degree than diabetes self-care. Finally, an emotion-focused intervention may be able to reduce both A1c levels and DD.